Implementation of Student Management at SMP Negeri 1 Seputih Banyak Central Lampung - Lilis Haryati; Subandi Subandi; Rina Mida Hayati (Assyfa Journal of Islamic Studies, 2025)
This study aims to analyze the implementation of student management at SMP Negeri 1 Seputih Banyak, Central Lampung Regency. Using a qualitative approach with a case study design, this research involved the principal, vice principal for student affairs, teachers, and educational staff as informants. Data collection techniques included in-depth interviews, participant observation, and documentation. The results showed that student planning has been implemented systematically based on data through analysis of student characteristics and needs. Student organization through recruitment and selection runs according to the principles of objectivity and transparency with a government policy-based admission system, while grouping is done randomly without superior classes. Coordination of student development runs collaboratively through the School Environment Introduction Period (MPLS) activities that effectively help student adaptation. Student supervision is conducted comprehensively including development, recording and reporting, to graduation and alumni management. This research contributes to the development of adaptive and integrated student management models at the junior high school level.